Socio-Philosophical Foundations of the Formation and Development of a Culture of Peace in the Context of Information Globalization - Umarova Feruza (Scientific Trends, 2025)
This article analyzes the impact of information globalization processes on the development of contemporary society, as well as the socio-philosophical foundations of the formation and development of a culture of peace under these conditions. The study interprets the expansion of the global information space, the widespread use of digital communication tools, and their influence on social consciousness as significant factors in establishing a culture of peace. Furthermore, the importance of tolerance, intercultural dialogue, social stability, and universal human values in the context of intensified information flows is examined through philosophical approaches. The article also substantiates, from a theoretical and scholarly perspective, the positive and negative aspects of information globalization processes, their influence on the culture of peace, and their role in ensuring social harmony and sustainable development in society.
Keywords: Information globalization, culture of peace, global information space, social consciousness, tolerance, intercultural dialogue, social stability, universal human values, philosophical analysis, digital society.